Immune Check Point Inhibitors and Immune-Related Adverse Events in Small Cell Lung Cancer - Hou, Wanting; Zhou, Xiaohan; Yi, Cheng; Zhu, Hong (Frontiers in Oncology, 2021)
Small cell lung cancer (SCLC) is a malignant solid tumor. In recent years, although immune check point inhibitors (ICIs) have achieved important advances in the treatment of SCLC, immune-related adverse events (irAEs) have occurred at the same time during the therapeutic period. Some irAEs lead to dose reduction or treatment rejection. The immune microenvironment of SCLC is complicated, therefore, understanding irAEs associated with ICIs is of great importance and necessity for the clinical management of SCLC. However, the lack of comprehensive understanding of irAEs in patients with SCLC remains remarkable. This review aims to provide an up-to-date overview of ICIs and their associated irAEs in patients with SCLC based on present clinical data.